Universal Screening of SARS-CoV-2 of Oncology Healthcare Workers — a Brazilian experience - Ismael, Carla (2020)
The first confirmed case of coronavirus disease 2019 (COVID-19) in Brazil and Latin America was reported on February 26, 2020, in São Paulo. The outbreak of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has placed unprecedented strain on health-care services worldwide. Asymptomatic health-care workers (HCW) are a potential source of SARS-CoV-2 transmission, especially to immunocompromised Oncology patients. Screening of these HCWs may help contain transmission and isolate only those who require it. At Centro de Terapia Oncológica (CTO), an Oncology clinic in Petrópolis, RJ —Brazil, all HCWs were screened for SARS-CoV-2 in order to isolate those who were asymptomatic/symptomatic and positive for the virus. They were all tested through IgM/IgG rapid testing and those who had symptoms were also tested with nasopharyngeal swabs for reverse transcription polymerase chain reaction (RT-PCR) tests besides IgM/IgG reactivity. Amongst the 60 tested employees, 4 were positive for SARS-CoV-2 and were isolated. This method may be useful for health-care services to detect asymptomatic HCW and maintain workers’ and patients’ health, as transmission probability could be reduced while avoiding becoming short-staffed during this time of crisis.